(untitled) (REMUNOM, 2025)
The toy library is an essential space in the training of future teachers, as it enables the understanding of play as a pedagogical practice. This study stems from a research project that investigates the significance of the toy library in the education of undergraduate pedagogy students, promoting meaningful experiences related to playfulness and child development. Our theoretical framework is based on authors such as Luckesi (2004), Cória-Sabini (2004), Santos (1997), and Kishimoto (2000), among others. The literature highlights the importance of the toy library in higher education, as it provides pedagogy students with playful experiences, allowing for a more reflective and practical training process. Thus, the toy library becomes an essential tool in preparing educators committed to meaningful and humanized pedagogical practices. The methodology adopted in this study combines both qualitative and quantitative approaches, employing bibliographic research techniques. A systematic literature review was conducted to examine how "toy libraries in universities" are addressed in theses and dissertations. For this purpose, the CAPES thesis and dissertation catalog was used, covering studies published between 1997 and 2023. Therefore, this study aims to describe and reflect on the relevance of the toy library in higher education and its influence on the training of future teachers.